CHILD PSYCHOLOGY : A CONTEMPORARY VIEWPOINT - HETHERINGTON E. MAVIS; PARKE ROSS D. (MC GRAW-HILL BOOK COMPANY NEW YORK, 1999)
The writers primary goal has to present the most important contemporary ideas and issues in child psychology in a way that all students will understand, enjoy and find useful in their lives and in some cases their professional careers.
Keywords: HUMAN DEVELOPMENT